2018
DOI: 10.1016/j.trsl.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin proteasome system as a potential therapeutic target for systemic sclerosis

Abstract: The present review aims to summarize available knowledge on the role of the ubiquitin-proteasome system (UPS) in the pathogenesis of scleroderma and scleroderma-related disease mechanisms. This will provide the reader with a more mechanistic understanding of disease pathogenesis and help to identify putative novel targets within the UPS for potential therapeutic intervention. Because of the heterogenous manifestations of scleroderma, we will primarily focus on conserved mechanisms that are involved in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…This is not surprising as MCHR1 modulates energy metabolism ( 11 ), likely in association with leptin ( 68 ). The biological process related to ubiquitination may affect SSc pathogenesis by modulating TGFβ signaling and TLR-dependent signaling ( 69 , 70 ). We also observed that the biological processes related to ECM remodeling and PDGF-BB signaling were perturbed when MCHR1 expression is silenced in NHDF, indicating that silencing of MCHR1 mediated the effects of PDGF-BB in the regulation of these genes, namely PDGFRA, PDGFRB, PDGFD, and MAPK9.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as MCHR1 modulates energy metabolism ( 11 ), likely in association with leptin ( 68 ). The biological process related to ubiquitination may affect SSc pathogenesis by modulating TGFβ signaling and TLR-dependent signaling ( 69 , 70 ). We also observed that the biological processes related to ECM remodeling and PDGF-BB signaling were perturbed when MCHR1 expression is silenced in NHDF, indicating that silencing of MCHR1 mediated the effects of PDGF-BB in the regulation of these genes, namely PDGFRA, PDGFRB, PDGFD, and MAPK9.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with an increase in new protein synthesis is the need to degrade unwanted proteins via the ubiquitin-proteasome system. Indeed, increased activity of this proteolytic complex has been reported in fibrotic lung (46) and other organs (7), and in Fibs treated with pro-fibrotic mediators (6, 8, 9). At the molecular level, increased expression of ubiquitin ligases as well as proteasome subunits and their activators has been reported in fibrotic tissue and Fibs, including those from IPF patients (1012).…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin-proteasome system (UPS) is responsible for degradation of misregulated and damaged proteins to maintain protein homeostasis, and plays an essential role in cell proliferation, aging, apoptosis, and other major cellular processes. 1 A major regulatory step in the UPS is ubiquitination, a posttranslational modification that consists of the addition of the highly conserved 76 amino acid ubiquitin to a target protein via an adenosine triphosphate (ATP)-dependent process. First, the ubiquitin-activating enzyme (E1) forms a transient high-energy thiol with ubiquitin's C-terminal glycine residue in an ATP-dependent manner, followed by the transfer of ubiquitin to the active-site cysteine residue on the ubiquitin conjugation enzyme (E2).…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin‐proteasome system (UPS) is responsible for degradation of misregulated and damaged proteins to maintain protein homeostasis, and plays an essential role in cell proliferation, aging, apoptosis, and other major cellular processes . A major regulatory step in the UPS is ubiquitination, a posttranslational modification that consists of the addition of the highly conserved 76 amino acid ubiquitin to a target protein via an adenosine triphosphate (ATP)‐dependent process.…”
Section: Introductionmentioning
confidence: 99%